Anticancer activity and biophysical reactivity of copper complexes of 2-(benzo[d][1,3]dioxol-5-ylmethylene)-N-alkylhydrazinecarbothioamides - Beckford, Floyd A. (2012)
A series of copper complexes were synthesized from benzo[d][1,3]dioxole-5-carbaldehyde (piperonal) thio-semicarbazones (RHpTSC where R=H, CH3, C2H5 or C6H5 (Ph)). The complexes show interesting variations in geometry depending on the thiosemicarbazone; a dinuclear complex [Cu(HpTSC)Cl]2, a mononuclear complex [Cu(RHpTSC)2Cl2] (R=CH3 or C2H5) and another mononuclear complex [Cu(PhHpTSC)(PhpTSC)Cl] was generated. The complexes bind in a moderately strong fashion to DNA with binding constants on the order of 10(4)M(‒1). They are also strong binders of human serum albumin with binding constants near 10(4) M(‒1). The complexes show good in vitro cytotoxic profiles against two human colon cancer cell lines (HCT-116 and HT29) and two human breast cancer cell lines (MCF-7 and MDA-MB-231) with IC50 values in the low millimolar concentration range.